2009
DOI: 10.1002/lary.20226
|View full text |Cite
|
Sign up to set email alerts
|

Middle turbinate flap for skull base reconstruction: Cadaveric feasibility study

Abstract: Harvesting of a vascular pedicle flap from the MT is feasible, albeit technically demanding. It should be considered as an alternative for the reconstruction of small defects of the fovea ethmoidalis, planum, and sella, particularly for patients for whom a reconstruction with vascularized tissue is desirable but the nasoseptal flap is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 19 publications
(28 reference statements)
3
102
0
4
Order By: Relevance
“…Radioanatomic studies and clinical case series have proven that the NSF can cover anterior cranial fossa, transsphenoidal, and transclival defects independently for patients greater than 14 years of age, with an average coverage of 25 cm 2 of surface area. [12][13][14] The NSF enjoys a high degree of success after skull base reconstruction (95 % and greater), and has reliably been used in multiple institutions and countries [15,16]. Modifications of the NSF have provided a myriad of reconstructive options with high success rates, from takedown and reuse of the NSF during revision surgery years after the primary surgery (95 %) [17], to creating a bilateral ''Janus flap'' for an extremely large dural defect (100 %) [18], to partial harvest of the NSF as a nasoseptal ''rescue'' flap (NSRF) to be used only in case of CSF leak (100 %) [19 • ].…”
Section: Nasoseptal Flapmentioning
confidence: 99%
See 3 more Smart Citations
“…Radioanatomic studies and clinical case series have proven that the NSF can cover anterior cranial fossa, transsphenoidal, and transclival defects independently for patients greater than 14 years of age, with an average coverage of 25 cm 2 of surface area. [12][13][14] The NSF enjoys a high degree of success after skull base reconstruction (95 % and greater), and has reliably been used in multiple institutions and countries [15,16]. Modifications of the NSF have provided a myriad of reconstructive options with high success rates, from takedown and reuse of the NSF during revision surgery years after the primary surgery (95 %) [17], to creating a bilateral ''Janus flap'' for an extremely large dural defect (100 %) [18], to partial harvest of the NSF as a nasoseptal ''rescue'' flap (NSRF) to be used only in case of CSF leak (100 %) [19 • ].…”
Section: Nasoseptal Flapmentioning
confidence: 99%
“…Cadaveric studies have shown that the ITF may cover the anterior skull base from the posterior table of the frontal sinus to the sella, with an average of 4.97 cm 2 surface area coverage [14,25]. The major disadvantages of the ITF are the decrease in surface area that the ITF can provide for skull base repair and the decrease in length for flap placement as compared to other locoregional vascularized flaps [24,26,27].…”
Section: Intranasal Flapsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14] Use of a nasal septal flap (NSF) has reduced the rate of complications and allowed increasing numbers of patients with skull base neoplasms to undergo curative surgical resections by means of minimally invasive techniques. 15 One drawback of this technique is the difficulty of stabilizing the multilayered reconstruction in place after its application.…”
Section: Introductionmentioning
confidence: 99%